Partial exclusivity can resolve the empirical puzzles associated with rent-seeking activities - Samuli Leppälä (Cardiff University, Cardiff Business School, 2018)
This study presents a model in which interest groups compete for partially exclusive rents and the number of winners is stochastic. Partial exclusivity can explain the low empirical estimates of rent dissipation that create the Tullock paradox. However,partial exclusivity also increases aggregate effort and social waste. This study includes an empirical analysis of U.S. state-level lobbying expenditures, which reveals another puzzle regarding the constant relationship between aggregate expenditures and the number of spenders. In contrast to the existing rent-seeking contest models, this outcome is consistent with partially exclusive rents when the contest is designed by a rent-seeking maximising policymaker.
Keywords: C72; D72; 330; rent seeking; interest groups; multiple-winner contests; rent dissipation; contest design; lobbying expenditures